“Comparative Evaluation of Torquing Movement of Upper Anterior Teeth Between Fixed Appliance And Clear Aligners With And Without Mini-Implants" - A FEM Study - Shukla, Shambhavi; Kallury, Amitabh; Jayade, Chetan; Balani, Rajesh Kumar; Jain, Shashank; Banerjee, Shounak (Journal of Neonatal Surgery, 2025)
Objective-The aim of this study was to compare the torquing movement of the upper anterior teeth between fixed appliance and clear aligners with and without mini-implant. Materials and Methods- It was a non-linear observational analysis study type. A CBCT scan of a healthy individual with an oversized axial inclination of the upper anterior teeth, along with extracted upper first premolars, was obtained from the CBCT center at People’s University, Bhopal. Results: This analysis has shown that model 3- clear aligner with power ridges on labiogingival and palatoincisal region, exhibited the highest von Mises stress measured at 0.13964 MPa whereas, model 4- clear aligners with mini-implant placed distal to the lateral incisors, recorded the maximum displacement measured at 1.30E-03mm. Conclusion: Overall, the clear aligners with auxiliaries like (power ridges and mini-implants) demonstrated more effective torque control than fixed appliances, offering a balance between force application and flexibility for controlled torque movement. In model 3, the displacement was measured at 6.61E-04 mm for the upper anterior teeth, and the individual teeth such as— the central incisors measured at 0.000749 mm, the lateral incisors measured at 0.0007295 mm, and canines measured at 0.0006415 mm, respectively. The model 4 exhibited the highest displacement, measured at 1.30E-03 mm for the total anterior teeth. The displacement values for the individual teeth as, the central incisors measured at 0.001615 mm, lateral incisors measured at 0.00146 mm, and canines measured at 0.000914 mm, respectively, were higher compared to the other models. In model 5, displayed second-highest displacement of 1.22E-03 mm for the upper anterior teeth. The central incisors measured at 0.001505 mm, the lateral incisors measured at 0.00137 mm, and the canines measured at 0.0008695 mm respectively